DESIGN AND IMPLEMENTATION OF WEB SERVICES FOR THE INTEGRATION OF INFORMATION SYSTEMS FOR THE DISTRIBUTION OF COVID-19 CASES - Ridwan Ridwan; Mira Maisura (UIN Ar-Raniry, 2020)
Several terms are used by the Government to collect data on the spread of covid-19's cases, namely People Under Surveillance (ODP), Patients Under Supervision (PDP), dead and positively infected. The Aceh government provides information on the spread of the covid-19 case through the official website media. Data of the cases are displayed daily based on the reports from districts / cities. District / city governments provide information based on reports from hospitals, health centers and from existing posts in each village. The unavailability of a data collection information system that can be used jointly in recording the spread of Covid-19 cases can lead to data duplication, because data collection is carried out according to individual needs. To overcome this problem, it is necessary to design and build a dissemination information system that can be used jointly between the village posts, sub-district offices, community health center (puskesmas) and hospitals. This research produces a website-based information system prototype for data collection on the spread of Covid-19 cases and API data services in the form of REST web services. Web Services are built using REST web services that generate request and response data using the JSON data format. The web services built can be used for integration with district / city and provincial government information systems, so that data changes can occur in real time.